Analysis of the effectiveness of performing technical actions to control the special training of arm-wrestler athletes - Markin, E.V.; Rakovetskiy, A.I. (Theory and Practice of Physical Culture, 2026)
Abstract Objective of the study is to identify the relationships between the indicators of activity, efficiency, effectiveness, and effective variability of the technical-tactical actions among student arm wrestlers. Methods and structure of the study. To determine the parameters for analyzing competitive activity, a pedagogical observation was conducted of the competitive and training process of the arm-wrestling athletes of the national team of the Russian State Agrarian University – Moscow Timiryazev Agricultural Academy. Video recordings of 145 bouts held in the period from 2024 to 2025 at all-Russian and regional competitions among students were studied. The level of technical-tactical preparedness of the arm wrestlers was assessed by the effectiveness of performing technical actions, the starting position, and the attacking action. The identification of the connections between the indicators of technical-tactical preparedness was carried out using correlation analysis. Results and conclusions. All the indicators of technical-tactical preparedness in arm wrestling were interconnected. The efficiency of performing technical actions varied depending on the presence of classification groups and successfully performed technical actions. In turn, the effective variability was connected with effectiveness (0.58) and activity (0.52). Effectiveness was also connected with activity (0.55), i.e., a change in the number of points in competitions entailed a change in the number of successful attempts to perform attacking techniques. In the course of the training process, coaches need to conduct conditioned sparring with various tactical tasks against fighters with oppositely named basic stances. It has been established that the combination of technical-tactical actions increases the volume, efficiency, and effectiveness of the technical-tactical arsenal of the athletes, giving arm-wrestling athletes a tactical advantage in conducting bouts.